O cordel no mercado editorial brasileiro das adaptações literárias (2000-2020) - Souza, Irany André Lima de (2022)
The adaptations, historically, has contributed for circulation and constant revitalization of the literature and has won attention as area of analysis. In this context, we observe the lack of studies over the cordel, gap what we aim fill with our doctoral research. Therefore, with this work, we have the goal to introduce the current panorama of literary adaptations in cordel in Brazil, emphasizing the period from 2000 to 2020. For this, we organize our thesis of approach quali- quantitative in three chapters: in the first, from bibliographic research, we exposed theoretical conceptions about adaptation, showing the critical fortune about her, both in the broadest sense and with respect only to the literature. In the next chapter, we present the context of adaptations in cordel, in Brazil, disclosed by Brazilian publishers until 2020. In chapter 3, we analyze the production and literary circulation of cordel in Brazil through the publication of adapted texts in publishing houses (from 2000 to 2020). In this part, through exploratory research and the documentary procedure, we did a data survey, your description and analysis, reaching 52 Brazilian publishers publishing adaptation in cordel in the support of the brochure or in book. Lastly, in order to understand better the dynamics of negotiations about the production and circulation of adaptations in cordel, we confront the information acquired in the publishers with interviews carried out by e-mail with 6 cordelistas: Cícero Pedro de Assis, Evaristo Geraldo da Silva, Francisco Paiva das Neves, João Bosco Bezerra Bonfim, Marco Haurélio e Rouxinol do Rinaré – and with editors from 3 companies – Amir Piedade, from Cortez Editora; Tatiana Fulas, from Panda Books; and Lucinda Azevedo, from Editora IMEPH. With theoretical and empirical data, we trace a more real panorama the context of publications of contemporary adaptations in cordel in the Brazilian publishing market, evidencing, at the same time, a fragment of the history of reading in Brazil, once we ratify the vitality of cordel literature dialoguing with a vast literary repertoire and adapt to new market demands, expanding your reach. To carry out this research, part of our theoretical contribution is based on studies of (1999; 2004; 2006), Galvão (2001), Luciano (2012) and Haurélio (2018), about cordel literature and in studies carried by Hutcheon (2013), Carvalho (2006), Formiga (2009), Coelho (2010) and Feijó (2010) about adaptations.